Working practices and success of infection prevention and control teams: a scoping study. Issue 2 (February 2015) - Hale, R.; Powell, T.; Drey, N.S.; Gould, D.J.
Summary Little research has been undertaken on how infection prevention and control (IPC) teams operate and how their effectiveness is assessed. This review aimed to explore how IPC teams embed IPC throughout hospitals, balance outbreak management with strategic aspects of IPC work (e.g. education), and how IPC team performance is measured. A scoping exercise was performed combining literature searches, evidence synthesis, and intelligence from expert advisers. Eleven publications were identified. One paper quantified how IPC nurses spend their time, two described daily activities of IPC teams, five described initiatives to embed IPC across organizations following legislation since 1999 in the UK or changes in the delivery of healthcare, and three explored the contribution of IPC intermediaries (link nurses and champions). Eight publications reported research findings. The others reported how IPC teams are embedding IPC practice in UK hospitals. In conclusion, there is scope for research to explore different models of IPC team-working and effectiveness, and cost-effectiveness. Other topics that need addressing are the willingness and ability of ward staff to assume increased responsibility for IPC and the effectiveness of intermediaries.